In search of possibilities : Informal responding to domestic violence - Palmer, Marilyn (2005)
This thesis is based on a feminist ethnography. designed to explore how we as members of informal networks (family, social,,student/work and neighbourhood networks) can respond usefully where there is domestic violence. Here, domestic violence refers to violence against women by their intimate partners and I have filtered the various discourses which seek to explain domestic violence through the lens of a feminist ecological model. The inquiry process has been informed by a postmodem feminism. Non-foundationalist ideas about knowledge have influenced the gathering, interpretatation and representation of the research data. The ideas which emanate from the stady have been informed by the view that language, embodied and as text, plays a pivotal role in shaping how we live in the world and how we socially construct our world through interactions with others. The ways in which particular discourses govern what it is possible for us to say and do around domestic violence have been a focus for the study